Coordinated Signal Control System in Urban Road Network - Rida, Nouha; Ouadoud, Mohammed; Hasbi, Abderrahim (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Road congestion has become one of the major problems of urban cities due to the growth in the number of vehicles and the limitation of road infrastructure. The consequences of this congestion can be seen through a difficult movement of vehicles, an increase in CO2 emissions, increasing energy consumption, and stress for drivers. Intelligent Transport Systems (ITS) based on wireless sensor networks (WSN) have emerged with new solutions and application potentials in the context of the Intelligent city.  In this article, we study an approach of using a wireless sensor network to control the traffic lights of several intersections and optimize their performance by reducing the average waiting time of users. the proposed adaptive traffic light controller determines the traffic lights sequence in real time based on the current traffic situation at the local intersection, the expected arrivals and the degree of congestion at destination intersections. To evaluate our approach, we construct an intersection network of twenty-four intersections with high traffic intensity using the SUMO simulator, the results of the simulation demonstrate the efficiency and practicality of the proposed algorithm.